2011
DOI: 10.1142/s0219633611006657
|View full text |Cite
|
Sign up to set email alerts
|

A DFT STUDY ON THE HYDROLYSIS MECHANISM OF THE NAMI-A-TYPE ANTITUMOR COMPLEX (HL)[trans-RUCl4L(dmso-S)](L=4-amino-1,2,4-triazole)

Abstract: The hydrolysis process of Ru (III) complex (HL)[trans- RuCl 4L(dmso-S)] (L=4-amino-1,2,4-triazole) (1), a potential antitumor complex similar to the well-known antitumor agent (ImH)[trans- RuCl 4(dmso-S)(Im)](NAMI-A), was investigated using density functional theory (DFT) with the conductor-like polarizable continuum model (CPCM). The structural characteristics and the detailed energy profiles for the hydrolysis processes of this complex were obtained. For the first hydrolysis step, complex 1 with 4-amino-1,2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Numbers in bold mean that the corresponding bond is most reactive in the studied compounds the BDE of the N 2 -N 3 bond is 50.4 kcal/mol, which is larger than that of the C 5 -N 5 bond and smaller than that of the C 1 -N 1 bond. For compound (5), the BDEs of the C 1 -N 1 and C 5 -N 5 bonds are equivalent and are all equal to 60.9 kcal/mol, while the BDE of the C 2 -N 2 bond is 87.4 kcal/mol. The BDEs of the C 1 -N 1 and C 5 -N 5 bonds are also equivalent for compound (6) and is equal to 61.3 kcal/mol, which is larger than that of the C 3 -N 3 bond.…”
Section: The Bond Dissociation Energies Of Several 124-triazole Dermentioning
confidence: 99%
See 2 more Smart Citations
“…Numbers in bold mean that the corresponding bond is most reactive in the studied compounds the BDE of the N 2 -N 3 bond is 50.4 kcal/mol, which is larger than that of the C 5 -N 5 bond and smaller than that of the C 1 -N 1 bond. For compound (5), the BDEs of the C 1 -N 1 and C 5 -N 5 bonds are equivalent and are all equal to 60.9 kcal/mol, while the BDE of the C 2 -N 2 bond is 87.4 kcal/mol. The BDEs of the C 1 -N 1 and C 5 -N 5 bonds are also equivalent for compound (6) and is equal to 61.3 kcal/mol, which is larger than that of the C 3 -N 3 bond.…”
Section: The Bond Dissociation Energies Of Several 124-triazole Dermentioning
confidence: 99%
“…Bond dissociation energies (BDE, kcal/mol) of some isomeric structures of the compound 5 at B3LYP/6-31G** level. The bold-faced number means that the corresponding bond is most reactive in the studied compound (5), which are the weakest bonds. A possible explanation for the above behaviour is that the presence of the weak interaction between O atom of nitro group and adjacent hydrogen atom, weakens the C-NO 2 bond length.…”
Section: The Bond Dissociation Energies Of Several 124-triazole Dermentioning
confidence: 99%
See 1 more Smart Citation
“…Similar behavior has been previously reported for NAMI-A, 85 where the hydrolysis mechanism is a stepwise process, as both a chloride and DMSO are lost. 86 While computational studies have suggested chloride ligand exchange to be prominent, 87,88 experimental studies have demonstrated that the DMSO is lost preferentially. 60,82 Previous EPR studies of Ru-P1 and Ru-P2 provide additional supportive evidence that the DMSO ligand is predominantly lost during the first step, while subsequent aquation leads to several soluble poly-aquated derivatives.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It is well-known that the solvent polarity influences both the structure and properties of conjugated organic molecules and metal complexes [53][54][55]. The structural data for the optimized structures of W(CO) 5 -pyridine-π-acceptor complex in six studied solvents are gathered in Table 2.…”
mentioning
confidence: 99%